Eco-friendly and rapid extraction of gold by in-situ catalytic oxidation with N-bromosuccinimide. Issue 6 (June 2022) - Liu, Xiang; Wang, Yongliang; Xiao, Li; Ma, Licheng; Han, Peiwei; Ye, Shufeng
Abstract: Gold is a valued, critical element whose chemical activation or extraction is challenging. Non-cyanide extraction of gold is now the focus, and N-bromosuccinimide(NBS) is attracting attention. Herein, new insights into the possible mechanism are deeply revealed through comprehensive analysis and detection of the reaction by using elementary gold and gold bearing ore. Experiments on gold foil indicate that Au can be activated in NBS solution to perform a satisfactory dissolution. Application of NBS in gold extraction from ore show a high yield of 86.24% under optimal conditions of NBS dosage 0.05 M, liquid-solid ratio 4:1, stirring speed 400 rpm, pH 8, 25 °C and leaching for 20 h, while yields of other coexisting metals are nearly negligible. The process leads to direct, efficient, one-pot conversion of gold, into simple water-soluble salts. Characterizations show that the framework of NBS are not destroyed, only bromine separates from the framework. The oxidation of neutral gold atom to trivalent Au (III) occurs in a mild, clean and room-temperature chemistry, which converts gold to [AuBr4 ] -, and the framework to succinimide. The active bromine and radical Br (Br) generated from in-situ autocatalysis of NBS are responsible for this. The systematic results herald a green procedure for preparation of gold derivatives and gold extraction industry. Graphical abstract: Image 1 Highlights: Utilizing nitrogen heterocyclic to carry bromine and sustainably release Br to in situ catalytically oxidize gold. One-pot conversion and high-efficient option to extract gold in a mild, clean and room-temperature chemistry. Bromine separates from NBS skeleton to generate Br and active Br2 and rapidly oxidized Au 0 to Au 3+ to form stable complex compound [AuBr4 ] - . High Au leaching selectivity with 86.24% yield by 0.05 M NBS and nearly negligible yields of other coexisting metals. Abstract : Gold extraction; In-situ autocatalysis; Non-cyanide; NBS; Oxidative etching.